Pengaruh Lingkungan Kerja dan Motivasi terhadap Kinerja Karyawan pada PT. Central Kuta Money Exchange - Diah Pratiwi, I Gusti Ayu; Hartati, Ni Putu Sri; Oktarini, Luh Nik (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
This research was conducted at PT. Central Kuta Money Exchange. The number of samples used were 50 respondents. Data collection techniques are observation, interviews, documentation, literature and questionnaires. While the data analysis techniques are validity, reliability, classic assumption test, multiple linear regression analysis, determination, t test (t test), and f test (f test). The test results show that there is a positive and significant influence between the work environment on employee performance at PT. Central Kuta Money Exchange seen from the results of the t-test obtained t1-count is 4.432 which is greater than the t-table of 1.684 and a sig value of 0.000. There is a positive and significant influence between motivation on employee performance at PT. Central Kuta Money Exchange seen from the results of the t-test obtained t2-count is 4.834 which is greater than the t-table of 1.684 and a sig value of 0.000. There is a positive and significant influence between work environment and motivation on employee performance at PT. Central Kuta Money Exchange seen from the F-count is 29.480 greater than the F-table of 3.23 and a sig value of 0.000.